Functional characterization of succinyl-CoA synthetase in the bloodstream form of Trypanosoma brucei - Kubišová, Karolína (Jihočeská univerzita, 2019)
During the infectious bloodstream stage (BF), the human pathogen Trypanosoma brucei lacks a canonical cytochrome-mediated respiratory chain. Therefore, this form of the parasite depends on the reverse activity of the FoF1-ATP synthase to hydrolyze ATP and pump protons into the mitochondrial intermembrane space to maintain the essential membrane potential. The dogma also states that the sole source of organellar ATP is the mitochondrial ADP/ATP carrier, which imports glycolytically derived ATP from the cytosol. In this study, we explore the possibility that the BF mitochondrion is able to contribute to its own pool of consumable ATP by utilizing an active succinyl-CoA synthase to generate ATP via substrate phosphorylation.
Functional characterization of succinyl-CoA synthetase in the bloodstream form of Trypanosoma brucei